Behaviour of Freelance Tour Guides in Promoting Ijen Crater Packages to French Tourists - I Gusti Putu Bagus Sasrawan Mananda; I Wayan Kartimin (STIE Pariwisata API Yogyakarta, 2024)
This study aims to identify the behavior of French-speaking freelance tour guides in promoting tour packages to Ijen Crater, Banyuwangi, and measure the effectiveness of the digital marketing strategies used. The research methodology employs a descriptive qualitative approach with primary data sources consisting of in-depth interviews with 5 freelance tour guides and 5 French tourists. The results indicate that freelance tour guides specialize in adventure activities and possess deep cultural knowledge. French tourists are attracted to the